2016
DOI: 10.1002/joc.4615
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal change of South China Sea summer monsoon intensity in the mid‐1990s

Abstract: This study analysed the interdecadal variation of the South China Sea summer (June–September) monsoon (SCSSM) in recent 32 years (1979–2010). The SCSSM showed a strengthening interdecadal variability starting from 1995, which was also verified in time series of precipitation and precipitable water averaged over the SCSSM domain. Thus, 32 years of total analysis period was divided into two: first half of past 16 years (1979–1994, hereafter 7994) and recent 16 years (1995–2010, hereafter 9510) thereby analysing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…To verify the change in the connection between the IPWP and the SCSSM, figure 3 shows the normalized WPSI and SCSSM intensity index during May (figure 3(a)) and the sliding correlation coefficients between the two indices with a window of 31 years ( figure 3(b)). The strength of the SCSSM (figure 3(a)) has increased since the 1990s, which is consistent with the findings of previous studies (Kwon et al 2007, Wang et al 2009, Choi et al 2017. The 31 year sliding correlation coefficients between the SCSSM intensity index and the WPSI has experienced a remarkable shift since the late 1980s ( figure 3(b)).…”
Section: Strengthened Relationship Between the Ipwp And Scssm Since Tsupporting
confidence: 89%
See 3 more Smart Citations
“…To verify the change in the connection between the IPWP and the SCSSM, figure 3 shows the normalized WPSI and SCSSM intensity index during May (figure 3(a)) and the sliding correlation coefficients between the two indices with a window of 31 years ( figure 3(b)). The strength of the SCSSM (figure 3(a)) has increased since the 1990s, which is consistent with the findings of previous studies (Kwon et al 2007, Wang et al 2009, Choi et al 2017. The 31 year sliding correlation coefficients between the SCSSM intensity index and the WPSI has experienced a remarkable shift since the late 1980s ( figure 3(b)).…”
Section: Strengthened Relationship Between the Ipwp And Scssm Since Tsupporting
confidence: 89%
“…Moreover, (Huangfu et al 2015) suggested that the interdecadal warming of the western Pacific warm pool results in an earlier outbreak of the SCSSM in the late 1990s by inducing stronger convection anomalies and weak WPSH in the early spring. Compared to the SCSSM onset date, relatively few studies have focused on the relation between the variability in the SCSSM intensity (Wu et al 2003, Wang et al 2009, Choi et al 2017 and the thermal state of the IPWP. (Choi et al 2017) found an enhancement in the SCSSM intensity during the mid-1990s and attributed it to strengthening of the Walker circulation and La Niña events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Q4-related rainfall over SEC is small in 1960s-1980s and it becomes most pronounced during 1993-2002 with a maximum in 1998. Such an interdecadal trend coincide with the increasing occurrences of severe flooding over SEC since mid-1990s (e.g., Kajikawa and Wang 2012;Choi et al 2017). Overall, the rainfall amount related to Q4 occurrence (~20% summer days) contributes ~30% of the summer total rainfall at 27-31°N (Fig.…”
Section: Interannual/interdecadal Variations Of Rainfall Associatementioning
confidence: 66%